Isotherms and Kinetics Study for Adsorption of Nitrogen from Air using Zeolite Li-LSX to Produce Medical Oxygen - Mohammed Ali, Marwa Hussein; Almilly, Raghad F.; Abid, Riyadh Kamil (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
This research investigates the adsorption isotherm and adsorption kinetics of nitrogen from air using packed bed of Li-LSX zeolite to get medical oxygen. Experiments were carried out to estimate the produced oxygen purity under different operating conditions: input pressure of 0.5 – 2.5 bar, feed flow rate of air of 2 – 10 L.min-1 and packing height of 9-16 cm. The adsorption isotherm was studied at the best conditions of input pressure of 2.5 bar, the height of packing 16 cm, and flow rate 6 Lmin-1 at ambient temperature, at these conditions the highest purity of oxygen by this system 73.15 vol % of outlet gas was produced. Langmuir isotherm was the best models representing the experimental data., and the model parameters were the maximum monolayer coverage (qm) 200 mg. g-1 and Kl 0.00234 L.mg -1. Also, from the Freundlich isotherm model, the sorption intensity (n) indicated favorable sorption of 1.435. The average free energy estimated from the DRK isotherm model was 0.02 KJ.mol-1, which proved the adsorption process to follow physical nature. The results got from experiments showed a coincidence to the pseudo-first-order kinetic model.